Circular Public Procurement: Inovasi Transformasi Tata Kelola Menuju Indonesia Berkelanjutan - Ardytania, Dinda; Bandiyono, Agus (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2025)
The amount of national expenditure related to the procurement of goods and services in the public sector has a significant influence because it includes the procurement of goods and services on a national scale which has an impact on various economic and development sectors. In this context, Circular Public Procurement (CPP) can be an innovative concept that supports the circular procurement of goods and services to create demand for products or services that support aspects of the circular economy, such as reusability or recycling. This research aims to analyze the steps involved in implementing CPP practices, analyzing the implementation of CPP practices in other countries, and analyzing the opportunities and challenges of implementing CPP practices in Indonesia. This research uses a literature study through a scoping review to collect information from the scope of the research and assess how the research topic that can be the basis of this research has developed in the last ten years. The results of this research indicate that CPP practices can be implemented in stages. Several countries such as the Netherlands, Denmark, Spain, and Sweden have adopted CPP practices through different approaches. In Indonesia, implementing CPP practices has opportunities and challenges in becoming a circular public procurement innovation. Therefore, the government is advised to create special regulations or policies regarding the implementation of CPP practices to address environmental, economic, and government governance issues.